2021
DOI: 10.14719/pst.1367
|View full text |Cite
|
Sign up to set email alerts
|

Impact of habitat variability on growth dynamics of Bergenia ciliata (Haw.) Sternb. along an altitudinal gradient in Kashmir Himalaya

Abstract: Bergenia ciliata (Haw.) Sternb. is an important medicinal plant of the Himalayan region. Phenotypic attributes of a particular plant species varies along different altitudes in order to adapt and to overcome the changeable and stressful conditions. A number of environmental factors such as mean temperature, precipitation, soil characteristics, radiation intensity etc. changes with altitudinal gradient and thereby affect the morphological pattern of a plant species. The present study was undertaken to reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Which ultimately results in an overall decrease in plant size. This reverse relationship between plant height and increasing altitude, as an adaptation has already been reported by various workers [21][22][23][24]. Apart from the severe conditions, plants growing at high altitudes have shorter growing seasons, which are less tall compared to plants at lower altitudes, where the growth period is relatively longer [25,26].…”
Section: Effect Of Elevation and Habitat On Phenotypic Traits Of Bist...mentioning
confidence: 55%
“…Which ultimately results in an overall decrease in plant size. This reverse relationship between plant height and increasing altitude, as an adaptation has already been reported by various workers [21][22][23][24]. Apart from the severe conditions, plants growing at high altitudes have shorter growing seasons, which are less tall compared to plants at lower altitudes, where the growth period is relatively longer [25,26].…”
Section: Effect Of Elevation and Habitat On Phenotypic Traits Of Bist...mentioning
confidence: 55%
“…During the current study, it is observed that there is a discrete as well as directional vogue towards morphology, structural design, and characters associated with fitness among different surveyed populations of P. cashmeriana thriving at various altitudinal ranges. Noteworthy variability in phenotypic characters was documented and a general trend [25] being one of the distinguished phenomena towards plant adaptation at increasing altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Elevational gradients thus provide an appropriate scenario to study these responses and important characteristics that are required for the proper functioning of plants in varying habitats [2]. The study of seed germination methods and seed dormancy are important in understanding survival, regeneration, plant community establishment, and adaptations of plants to changing climatic conditions [3][4][5][6][7]. The association between plant regeneration from seeds and climate has resulted in the evolution of distinct germination needs across species [8], and this, in turn, plays a critical role in establishing vegetation type and plant distribution [9].…”
Section: Introductionmentioning
confidence: 99%